Upaya Meningkatkan Ketuntasan Belajar Memastikan Kebutuhan Akan Dokumen Melalui Penerapan Pembelajaran Koopratif Model Student Teams Achievement Divisions (STAD) Pada Siswa Kelas XII APK-1 SMK Negeri 1 Magetan Pada Tahun Pelajaran 2010/2011 - Arum Yuliani (Universitas PGRI Madiun, 2019)
One of the topics of discussion among teachers, especially in the Office Administration Expertise Program of SMK Negeri 1 Magetan is the problem of managing learning by grouping students who sometimes experience obstacles and do not carry out as expected. This resulted in the results of group work becoming less than optimal and only a small percentage of students understood the group assignment material. As a result, when there is a test, there are still many students who get less grades from KKM or have not yet finished learning and classical learning completeness has not been achieved. This research is planned in three cycles. Each cycle consists of four stages, namely (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of the study were obtained (1) The application of STAD model cooperative learning can improve learning completeness to ensure the need for documents in class XII APk-1 SMK 1 Magetan in the academic year 2010/2011, (2) Application of STAD model cooperative learning can improve group learning activities in ensuring the need for documents in class XII APk-1 students at SMK Negeri 1 Magetan in the academic year 2010/2011, and (3) the application of STAD model cooperative learning is fun and can encourage students of class XII APK-1 at SMK Negeri 1 Magetan in the 2010 school year / 2011 to diligently study on basic competencies Ensuring the Need for Documents.